Reaction of CO2 With Alcohols to Linear-, Cyclic-, and Poly-Carbonates Using CeO2-Based Catalysts - Tomishige, Keiichi; Gu, Yu; Nakagawa, Yoshinao; Tamura, Masazumi (Frontiers in Energy Research, 2020)
Reaction of CO2 with alcohols to organic carbonates is one of non-reductive CO2 conversion methods. The catalysts are needed for this reaction, at the same time, effective H2O removal methods are also needed because the yield of organic carbonates is strongly limited by the equilibrium. The development of heterogeneous catalysts for the synthesis of dimethyl carbonate from CO2 and methanol, which is a model and typical reaction, is described. This is because heterogeneous catalysts are more suitable to the practical process than homogeneous catalysts from the viewpoint of the separation of catalysts from the products and the reusability of the catalysts. One of the reported heterogeneous catalysts is CeO2, and it has been also reported that the combination of dimethyl carbonate synthesis from CO2 and methanol with the hydration of nitriles such as 2-cyanopyridine, where both reactions are catalyzed by CeO2, enabled high yield of the carbonate. In addition, the combination of CeO2 catalyst + nitriles can be applied to the synthesis of a variety of linear-, cyclic (five- and six-membered ring)-, and poly-carbonates from CO2 and corresponding alcohols.